Community Assemblages of macrobenthic invertebrates in Batang Kayan and its tributes, Lundu, Sarawak - Nurul Hanim, Binti Adanan (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Community assemblages of macroinvertebrate at 7 sampling stations in Batang Kayan and its tributaries was constructed. U iOg macroinvertebrate as an indicator species, Average Score Per Taxon (ASPT) and Taxa Richness of Ephemeroptera, Plecoptera and Trichoptera (EPT) were conducted to evaluate the water quality status at each station. The low abundance of EPT organism indicates that study area was heavily disturbed. The status of watcr quality ranged from moderately polluted to polluted water. A total of 51 0 individuals was collected from the study area consisted of 4 classes, 12 orders and 18 families. Environmental parameters such as pH, dissolved oxygen, turbidity and depth of each station was used to evalualt: the distribution of macroinvertebrate. Analysis of variance (ANDV A) was conducted to reveal the significant dinerence among stations. Eventually, there were no differences of mean population among each sampling stations. Functional Feeding Group (FFG) was also conducted to review its influence in the distribution and community structure of macroinvertebrate in Batang Kayan . Gathering collector feeding group was found to be abundant almost in all sampling station and mainly dominated by Family Lumbriculidae and Dpistocystidae